2002
DOI: 10.1002/sce.10021
|View full text |Cite
|
Sign up to set email alerts
|

Reforming primary science assessment practices: A case study of one teacher's professional development through action research

Abstract: Calls for reform have suggested that classroom practice can best be changed by teachers who engage in their own research. This interpretive study examines the process of action research and how it contributes to the professional development of a first-grade teacher. The purpose of the study was to explore the research process experienced by the teacher as she examined whether portfolios could be used as an effective means for facilitating and assessing young children's development of science process skills. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In particular, the teachers found that each one felt a spirit of community. The point on collegial support echoes findings from previous studies such as Briscoe and Wells (2002), Burbank and Kauchak (2003) and Kraft (2002) and seems an essential component for supporting teachersí learning and professional development. One teacher, for instance, mentioned, ìI really enjoyed and learned from everyone in the course.î The other teacher said, ìThe interaction that we had was valuable.…”
Section: Socialsupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, the teachers found that each one felt a spirit of community. The point on collegial support echoes findings from previous studies such as Briscoe and Wells (2002), Burbank and Kauchak (2003) and Kraft (2002) and seems an essential component for supporting teachersí learning and professional development. One teacher, for instance, mentioned, ìI really enjoyed and learned from everyone in the course.î The other teacher said, ìThe interaction that we had was valuable.…”
Section: Socialsupporting
confidence: 79%
“…Moreover, they become part of the educational reform process as they are empowered to change and initiate change and apply new ideas. Furthermore, action research can bridge the gap between theory and practice because it helps teachers to understand the purpose of educational research and, in turn, informs educational theory of the reality of the classroom (Briscoe & Wells, 2002). In addition, teachers are empowered by having ownership of their professional knowledge.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Nevertheless, we have no direct data on her actual practice. A teacher's reflection on his or her own conceptions is known to be an important factor for there to be a beginning toward changing classroom practice (Briscoe & Wells, 2002). Several studies have found, however, that, depending on the teacher and the context, conceptions and practices are often out of phase with each other, and even plainly in contradiction, and that changes in one are not necessarily accompanied by a change in the rest (Freitas et al, 2004;Lederman, 1992;Marx, Freeman, Krajcik, & Blumenfed, 1998;Mellado, 1997Mellado, , 1998Meyer, Tabachnick, Hewson, Lemberger, & Park, 1999;Roehrig & Luft, 2004;Simmons et al, 1999;Solís & Porlán, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(Reflection a posteriori) We consider that there is a major educational potential in involving science teachers in research into important problems and situations of interest to them. Teachers will then be not mere consumers of external knowledge but co-producers and agents of change in the problems that really concern them (Briscoe & Wells, 2002). There have now been numerous examples of research of this nature.…”
Section: Methodology the Case Of Consuelomentioning
confidence: 99%
“…Teachers can critically examine the congruence, or lack thereof, between their espoused beliefs about teaching and learning and the beliefs in use that drive their practices (Briscoe, 1991;Clandenin & Conelly, 1987Elbaz, 1981Elbaz, , 1983. The possibility of practical change is enhanced because teachers develop a better understanding of themselves and their situation (Briscoe & Peters, 1997;Briscoe & Wells, 2002;Fenstermacher & Richardson, 1991;Richardson, 1994;Sparks & Simmons, 1989;Watts, 1985). Critical reflection among colleagues affords individuals opportunities to develop alternative ways of interpreting their reality and is considered to be an essential component of the development of teaching expertise at all levels (McLean & Blackwell, 1997;Wildman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%